203-LB: Redosing of Suboptimally Controlled Diabetic Mice with Human Neo-islets, 3D Aggregates of Mesenchymal Stromal and Pancreatic Islet Cells, Durably Restores Euglycemia: Relevance to the Treatment of Diabetic Humans - CHOWDHURY, SABIHA S.; GOOCH, ANNA; ZHANG, PING; HU, ZHUMA; WESTENFELDER, CHRISTOF (Diabetes (New York, N.Y.), 2020)
We reported that the i.p. administration of allogeneic Neo-Islets (NIs; 3D aggregates of allogeneic, culture-expanded Islet cells (ICs) with immune- and cyto-protective Mesenchymal Stromal Cells (MSCs)), durably restores normoglycemia in autoimmune type-1 diabetic NOD mice through omental engraftment. Similarly, our ongoing, FDA-guided pilot study in insulin dependent pet dogs (INAD 012-0776) demonstrates that allogeneic canine NI therapy significantly improves both glycemic control and insulin needs (> 1.5 years), and this without eliciting an allo-immune response. The current study was undertaken in preparation of a Phase I Clinical Trial in order to determine whether NIs engineered from human cells (hNIs) could also reduce insulin need, and whether redosing of suboptimally controlled diabetic mice could fully restore euglycemia, as is frequently required in human recipients of islet transplants. Hyperglycemia (blood glucose > 350 mg/dL x 3 days) was induced with streptozotocin in adult NOD/SCID mice and blood glucose levels were controlled with insulin pellets (Linbits) until i.p. hNI (2x10e5 hNIs/kg bw) or vehicle administration (n=6/group). Blood glucose levels, weights, ip glucose tolerance tests [GTT) were closely monitored. While no mice in the hNI treated group died (vs. 4 in the control group), hNI therapy partially reduced glucose levels . Therefore, on day 64 post initial treatment, mice were re-dosed with hNIs (2x10e5 hNIs/kg bw) and followed together with controls as above. This second dose of hNI completely and durably restored euglycemia and normalized ip GTTs. We conclude that this minimally invasive, safe and highly effective therapy supports our current pursuit of an IND for the conduct of a pioneering Clinical Trial in subjects with T1DM.